Health Security and Disease Prevention in Nigeria - Ekpenyong, M.J. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Health security is one of the most recent strategies of global initiatives in health promotion. This idea prompted the need to find out what the concept is all about. The write up therefore examined, the definition of health security, the initiation. issues of security threats globally in the aspect of communicable diseases and most especially the non communicable diseases, .efforts made by Nigeria in disease prevention, challenges encounteredso far, especially in the implementation of the reviewed International Health Regulations (IHR), suggestion for a way forward. The need of carrying out elaborate review in the aspect of health security, and putting up Medical Intelligence Surveillance (MIS) in place, use of mobile technology (M- Health) as well as strengthening the Nigerian health system was emphasized in the conclusion.